Clinical exome-based panel testing for medically actionable secondary findings in a cohort of 383 Italian participants - Martone, Stefania; Buonagura, Autilia Tommasina; Marra, Roberta; Rosato, Barbara Eleni; Del Giudice, Federica; Bonfiglio, Ferdinando; Capasso, Mario; Iolascon, Achille; Andolfo, Immacolata; Russo, Roberta (Frontiers in Genetics, 2022)
Background. Next-generation sequencing-based genetic testing represents a great opportunity to identify hereditary predispositions to specific pathological conditions and to promptly implement health surveillance or therapeutic protocols in case of disease. The term secondary finding (SF) refers to the active search for causative variants in genes associated with medically actionable conditions. Methods. We evaluated 59 medically actionable ACMG genes using a targeted in silico analysis of clinical exome sequencing performed in 383 consecutive individuals referred to our Medical Genetics Unit. A three-tier classification system of SFs for assessing their clinical impact and supporting a decision-making process for reporting was established. Results. We identified SFs with high/moderate evidence of pathogenicity in 7.0% (27/383) of analyzed subjects. Among these, 12/27 (44.4%) were carriers of a high-risk recessive disease allele. The most represented disease domains were cancer predisposition (33.3%), cardiac disorders (16.7%), and familial hypercholesterolemia (12.5%). Conclusion. Although still debated, ensuring during NGS-based genetic testing an opportunistic screening might be valuable for personal and familial early management and surveillance of medically actionable disorders, the individual’s reproductive choices, and the prevalence assessment of underestimated hereditary genetic diseases.